Childhood dental anxiety: Associated factors and management strategies (Research, Society and Development, 2026)
Childhood dental anxiety is one of the main challenges in pediatric dentistry, as it directly influences the child's behavior and can compromise treatment adherence and oral health throughout life. Factors such as previous negative experiences, presence of pain, socioeconomic characteristics, child temperament, and parental anxiety are among those most associated with the development of this condition. Non-pharmacological management strategies have shown effectiveness in reducing anxiety and improving child cooperation. This study aims to analyze the factors associated with childhood dental anxiety, its consequences on behavior and treatment adherence, and the effectiveness of the main non-pharmacological management strategies described in the literature. This study is characterized as a narrative literature review, of a descriptive and exploratory nature, which was carried out through searches for articles published between 2000 and 2025, in Portuguese, English, and Spanish, in the PubMed, Scielo, Lilacs, and Google Scholar databases. Analysis of the studies demonstrates that childhood dental anxiety is related to various emotional, behavioral, and family factors, and can negatively interfere with a child's cooperation during dental treatment. It is also observed that the use of non-pharmacological strategies contributes to reducing anxiety and promotes a more calm and humane treatment experience.